INFLUENCE OF MANUFACTURE OF THE WINDOW AND THE FITTINGS USED ON THE FINAL QUALITY OF THE WINDOW - Jevtoska, Elena (My University, 2022)
The window as a product used in construction aims to provide natural light and the possibility for ventilation in the building where it is placed, but at the same time to protect the room from external influences such as wind and rain and to prevent uncontrolled cooling or heating of the building it is built-in. Given the purpose, a quality window is one that protects against air penetration, water penetration and it ensures wind resistance. The window is a complex product that is composed of different parts that can be made of different materials. As part of this research, windows made by different manufacturers and made from different materials will be tested, but they are with profile identical to the profile used for the frame and the window sash. The main goal is to prove whether the construction of the window and the fittings used have an impact on the final quality of the window. In order to do the research, ten windows will be tested in accordance with the European norms EN 1026: 2016 (test method for air permeability), EN 1027: 2016 (test method for water permeability), EN 12211: 2016 (test method for wind resistance).
Keywords: construction carpentry, window, air permeability, water permeability, wind resistance, PVC profiles.